Expanding Horizons in Bioethics - Galston, A.W; Peppard, Christiana Z. (Springer Netherlands : Imprint: Springer, 2005)
What are the resources and needs, the strengths and the vulnerabilities of patients, of society, or of nature? How do we evaluate the societal potential of scientific discovery? It is fairly well assured that we are influencing the terms of existence of many inhabitants of this planet, from flora to fauna to humans. Moreover, history has shown that while technologies can be used neutrally, they can be (and have been) used to the great benefit - or the great detriment - of human life and the fate of the world as a whole. How various types of knowledge and technological ability will be deployed is up to us, individually and collectively. How such information and ability should be deployed, and for what reasons, are questions at the core of bioethical inquiry. These are the "expanding horizons in bioethics" to which this volume refers. This volume is comprised of fourteen essays. It is a rare gathering of scholarly opinion, featuring well-known experts from a diversity of disciplines. The topics addressed are of immediate concern to the public. The essays ask questions about human nature, genetic technologies, reproductive rights, human subjects research, and environmental issues - all in provocative and challenging new ways. Yet the themes that emerge throughout the volume are of enduring interest to anyone concerned about the interactions of scientific development, ethics, and society. This volume is of interest to students and teachers of bioethics and related topics, as well as to professionals working in these disciplines. "The collection of essays makes an original contribution through the generally very high standard of scholarship of the papers, and through the engagement by those authors with very contemporary issues in bioethics... It is rare that so many highly original views are collected in one volume." Quote from a pre-publication review.